Impact of the Planning from the Kanban System on the Company’s Operating Beneﬁts - Mojarro Magaña, Maria (2018)
This article reports a model regarding the structural equations of the impact of the planning phase and the beneﬁts acquired in the implementation of the kanban system. It begins with a literature review of the activities of the planning phase, based on which a questionnaire was developed and applied in manufacturing companies in the state of Baja California, in the municipalities of Ensenada, Tijuana, Tecate, and Mexicali. The responses were obtained from 118 questionnaires and were validated by the Cronbach’s alpha index for internal validity and the R-squared index for predictive validity. A model of the structural equations of the planning phase was developed and validated through three latent variables, namely, human resources, preliminary analysis, and kanban integration, which correspond to 22 activities and one variable that integrate 11 operational beneﬁts. The model shows six hypotheses to verify the causal relationships between these variables. Partial least-squares algorithms are used to validate the hypothesis, and the results indicate that the preliminary analysis is the basis for the success of the implementation of the kanban in the planning stage, through the application of activities, such as 5’s, value stream mapping (VSM), material handling, ﬂow diagram, and visual aids with a sustainable approach, according to the efﬁcient ﬂow of materials and minimum downtime.